Mechanism of low-level Er:YAG laser irradiation involved in osteoblast proliferation - Pavlić Verica (Scripta Medica, 2010)
Background It has been reported that MC3T3-E1 osteoblast proliferation was enhanced following low-level Er:YAG laser irradiation (low-level laser therapy-LLLT, photo-bio-modulation). However, the reason for enhanced osteoblast proliferation following low-level Er:YAG laser irradiation remained unclear. Therefore, the aim of this study was to investigate the potential mechanisms underlaying photo-bio-modulatory effect of the Er:YAG laser on osteoblasts. Materials and Methods MC3T3-E1, mouse derived osteoblasts were irradiated at specific fluence of 2.6 mJ/ cm2 and, the role of mitogen-activated protein kinase (MAPK) pathways in laser-enhanced cell proliferation was examined. Results Low-level Er:YAG laser irradiation induced the phosphorylation of extracellular signal-regulated protein kinase (MAPK/ERK), and MAPK/ERK inhibitor U0126 significantly inhibited laser-enhanced cell proliferation. Conclusion These results obtained that low-level Er:YAG laser irradiation increases osteoblast proliferation mainly by activation of MAPK/ERK, suggesting that the Er:YAG laser may be efficient in promoting bone healing following periodontal and peri-implant therapy.